Proposição de um modelo multicritério de apoio a decisão para a seleção de fornecedores verdes no contexto do varejo - Souza, Cristiane Cardoso de (Universidade Federal Rural do Semi-Árido, 2020)
The environmental theme is increasingly present in all spaces and, due to a series of factors that include increased government regulation, stronger public awareness and market competitiveness, among others,environmental management has entered organizations, leading they seek to achieve better environmental performance as a way to remain competitive in the market. The selection of green suppliers is one of the practices adopted by organizations in order to improve their environmental performance and consists of considering, in addition to traditional criteria, environmental criteria in the process of choosing suppliers. As it is an activity of a complex nature and involves multiple criteria, the use of multicriteria decisionmaking approaches for selecting green suppliers is a viable alternative for companies that seek effectiveness in this choice process. Therefore, the objective of this research is to propose a decision model, based on multicriteria analysis, to assist the process of selecting green suppliers in the retail context, considering economic and environmental criteria, through the TOPSIS method. In addition, a sensitivity analysis was performed to prove the robustness of the method used. The model was tested through simulated application. The study adopted a quantitative approach, as for nature it is classified as applied, with regard to objectives as descriptive and exploratory and as for technical procedures, it is a case study. The result shows that supplier A4 ranks first among the five evaluated suppliers, demonstrating a strong environmental performance.
Keywords: Seleção de fornecedores; fornecedores verdes; MCDA; TOPSIS; ENGENHARIAS::ENGENHARIA DE PRODUCAO